EXECUTORIAL STRENGTH IN EXECUTION OF WARRANTY OBJECT OF DEBTOR'S DEBT IN FIDUSIAN AGREEMENTS IN THE ERA OF COVID -19 - Nelly Azwarni Sinaga; Humala Sitinjak; Mukidi Mukidi; Rudy Pramomo (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The period of the Covid 19 pandemic that has hit the world including Indonesia, which started the spread of this virus since the end of 2019, where the impact was tremendous for all human life, including the aspects of health, the economy including also affecting the implementation of agreements in legal aspects. The Fiduciary Agreement is a form of anonymous agreement that was born along with the development of business practices in Indonesia. The parties to the fiduciary agreement have mutually agreed to regulate their respective rights and obligations as well as legal sanctions if a party breaks the promise. This paper limits the problem regarding debtors who do not fulfill the agreement / break promises on the agreements that have been bound and the consequences for the object of the agreement. Consequences of debtors who break their promises result in Default. Problems arise when the fiduciary object is executed because the Debtor is in Default and the execution procedure is not properly carried out. This study aims to determine the legality of the execution of fiduciary collateral objects for debtors who are defaulting during the Covid 19 pandemic. auctions in public or can be carried out by selling under the hands of the agreement of both parties, but the implementation often still does not fulfill the mandate of the law or the agreement is not carried out properly. others that: 1. Communities who are not affected by economic constraints and other constraints in fulfilling their achievements 2. Communities who are affected by the economy and other constraints in fulfilling their achievements. Banks can provide credit / financing to obtain special treatment in accordance with applicable regulations